Public Relations Strategy In Improving The Image Of Iqra' 1 Integrated Islamic Primary School (SDIT) Bengkulu City - Evi Hafizah; Marlina, Neneng Cucu (Wardah, 2024)
Public Relations (PR) plays an important role in the school's reputation and the education delivery process. Public relations functions to support relationships and a good name to the community. This good relationship can help obtain public support so that students can realize the school's vision and mission. The research  method used is a case study, which will examine public relations strategies including planning, implementation and evaluation of activities carried out to improve the school's image. The results of the research show that the Public Relations strategy of SDIT Iqra' 1 in the city of Bengkulu carried out several stages including: 1) Planning, SDIT Iqra' 1 set specific, measurable and relevant goals, such as increasing recognition of academic achievements and strengthening relationships with the community. This plan includes developing a consistent message and choosing effective communication channels to reach the target audience. 2) Implementation, SDIT Iqra' 1 utilizes various media, including social media (Facebook, Instagram, and TikTok), digital tabloids, and radio broadcasts to disseminate information and reach a wider audience, then carry out social activities for the community such as the Friday sharing program and sharing sacrificial meat during the Eid al-Adha holiday, 3) The evaluation carried out by SD IT Iqra' 1 includes media analysis, long-term impacts, and community involvement.